ANTIOXIDANT ACTIVITY AND ITS CORRELATION OF DIFFERENT SOLVENT EXTRACTS OF MALE CONES OF Cycas beddomei Dyer, ENDEMIC TAXA TOSESHACHALAM BIOSPHERE RESERVE - M. MAHENDRA NATH; CH. SANTOSH; K. MADHAVA CHETTY (International Journal of Pharma and Bio Sciences, 2013)
Cycas beddomei Dyer. (Cycadaceae), is an endemic and critically endangered, tropical, dry deciduous, dioecious gymnosperm present in varied region of adjunct areas of Tirumala Hills, Seshachalam Biosphere Reserve, Southern Eastern Ghats, India. In vitro antioxidant studies by employing different parameters such as DPPH, TAC, ABTS and superoxide radical scavenging activity have been tested with different extracts viz., methanolic, ethyl acetate and n-Hexane. Screening for biochemical availability was done for flavonoids and phenolics and were evaluated statistically which showed positive correlations among biochemical availability and antioxidant activities with all the extracts. This study suggests that all the extractives showed antioxidant potency and laid a scientific proof that C. beddomei male cones are new potential source of natural antioxidants.